Images of the Mind and Images for the Eye. An Iconographical Approach to UFO-Mythology - Rothstein, Mikael (Scripta Instituti Donneriani Aboensis, 1996)
In the study of contemporary new religions and popular religious or metaphysical notions, the iconographical sources are often sadly overlooked. In this article it is the intention to present an iconographical approach to one single, although significantly versatile, aspect of modern, non-traditional mythology, namely the notion of "flying saucers" or UFOs (i.e. Unidentified Flying Objects). The actual UFO-religions may be insignificant in terms of adherence, but the very concept of UFOs holds a strong position in contemporary metaphysics and spirituality, as we find it in the so called New Age movement and elsewhere. Starting with the very notion of strange circular phenomena in the sky, a vast and very differentiated mythology of "flying saucers" or UFOs has developed. As far as the iconographical presentations reflect the narrative structure(s) of the UFO myth, these pictures are integrated elements of the UFO story, and sometimes even agents of a further ufological development.